Isolation and Characterization of Anthraquinone Derivatives from the Heartwood of Cassia glauca Lam. - RAI, K.N.; RANJAN, SANJEEV; S. CHANDRA, SATISH (Asian Journal of Chemistry, 2010)
Phytochemical examination of the heartwood of Cassia glauca resulted in the isolation of two new anthraquinone glycosides, 8-hydroxy- 6-methoxy-3-methyl anthraquinone-1-O-α-L-rhamnosyl(1→2)-β-Dglucoside (I) and 3-hydroxy-6,8-dimethoxy-2 methyl anthraquinone- 1-O-α-L-rhamnosyl(1→6)-β-D-glucoside (II). The known anthraquinone derivatives, chrysophanol (III), physcion (IV) and rubiadin (V) have also been isolated. The structural elucidations of all the isolated compounds were established on the basis of spectroscopic and chemical studies.